Toward a national animal telemetry network for aquatic observations in the United States. Issue 1 (December 2016) - Block, Barbara; Holbrook, Christopher; Simmons, Samantha; Holland, Kim; Ault, Jerald; Costa, Daniel; Mate, Bruce; Seitz, Andrew; Arendt, Michael; Payne, John; Mahmoudi, Behzad; Moore, Peter; et al.
Abstract Animal telemetry is the science of elucidating the movements and behavior of animals in relation to their environment or habitat. Here, we focus on telemetry of aquatic species (marine mammals, sharks, fish, sea birds and turtles) and so are concerned with animal movements and behavior as they move through and above the world's oceans, coastal rivers, estuaries and great lakes. Animal telemetry devices ("tags") yield detailed data regarding animal responses to the coupled ocean–atmosphere and physical environment through which they are moving. Animal telemetry has matured and we describe a developing US Animal Telemetry Network (ATN) observing system that monitors aquatic life on a range of temporal and spatial scales that will yield both short- and long-term benefits, fill oceanographic observing and knowledge gaps and advance many of the U.S. National Ocean Policy Priority Objectives. ATN has the potential to create a huge impact for the ocean observing activities undertaken by the U.S. Integrated Ocean Observing System (IOOS) and become a model for establishing additional national-level telemetry networks worldwide. Background Telemetry can provide environmental, behavioral and physiological data in near-real time, or by use of archival tags in which the data are stored or later transmitted to satellites. Aquatic animal species tagged have ranged from 6-g salmon smolts to 150-ton whales. Detailed observations of animal movements and behavior in relation to critical habitats in their aquatic environment have significantly improved our understanding of ecosystem function and dynamics. These observations are critical for sustaining populations, conserving biodiversity and implementing ecosystem-based management through an increased understanding of ecosystem structures, functions, and processes, as well as their importance to ecosystem services and values. Sensors carried by tagged animals have come of age and deliver high-resolution physical oceanographic data at relatively low costs. Animals are particularly adept at helping scientists identify critical habitats, spawning locations, and important oceanographic features (e.g., fronts, eddies and upwelling areas). They also provide important insights into regions of the oceans that are difficult and expensive to monitor (e.g., offshore environments, Arctic). This paper focuses on how to integrate an operational ATN into U.S. IOOS. Results The development of U.S. IOOS initially focused on the acquisition and integration of physical and chemical oceanographic data. With this system now operational, U.S. IOOS is ready to add the acquisition of relevant biological observations, and to enhance the acquisition of physical and chemical oceanographic observations via ATN platforms. Conclusion A U.S. ATN observing system that monitors aquatic life on a range of temporal and spatial scales could yield both short- and long-term benefits, fill oceanographic observing and knowledge gaps, and advance many of the National Ocean Policy Priority Objectives. ATN has the potential to create a huge impact for the ocean observing activities undertaken by IOOS and become a model for establishing additional national-level telemetry networks worldwide.